Islamic peace ethics : legitimate and illegitimate violence in contemporary Islamic thought - Shadi, Heydar, 1975- (Studien zur Friedensethik ;, 2017)
Proceedings of the International Workshop "Islamic Peace Ethics: Legitimate and Illegitimate Violence in Contemporary Islamic Thought", organized 15-17 October 2015 by the Institute for Theology and Peace (ithf), Hamburg. More than 20 researchers from different countries including Indonesia, Pakistan, Iran, Germany, UK, USA, and Belgium discussed the peace and war in contemporary Islamic thought from different disciplines such as theology, philosophy, religious studies, cultural studies, and political sciences. Sponsored by the Institut für Theologie und Frieden.